Effect of human activity on habitat selection in the endangered Barbary macaque. (22nd October 2019) - Waterman, J. O.; Campbell, L. A. D.; Maréchal, L.; Pilot, M.; Majolo, B.
Abstract: The exponential growth of human population and infrastructure is significantly reducing the amount of ecological resources available for wild animals. We analyzed the effect of human activity on Barbary macaques Macaca sylvanus, an endangered species restricted to the fragmented forests of Morocco and Algeria, using location data from five social groups inhabiting Ifrane National Park, Morocco. We used a resource selection function to explore the effects of anthropogenic disturbance on macaque habitat selection, using nine natural, social, and anthropogenic disturbance variables as predictors. Forest cover, home range overlap, herding route proximity, and road proximity were all significant predictors of habitat use. Macaques avoided areas used by local shepherds, to reduce the risk of attack by shepherds' dogs, but approached roads to increase the chances of provisioning by tourists. However, herding route and road use varied seasonally in line with levels of human use, suggesting that macaques may be navigating their environment strategically (in space and time) to balance food acquisition and risk avoidance. The results of this study highlight the importance of assessing human impact on habitat selection in both space and time. Our data on seasonal variations in macaques' use of roads can help prevent road injuries, a major source of mortality for provisioned macaques, by focusing management efforts by national park workers in time and space. Furthermore, understanding when and where macaques seek provisioning from tourists can help combat provisioning, which negatively impacts macaque health, behavior, and susceptibility to poaching. Abstract : We analyzed the effect of human activity on Barbary macaques Macaca sylvanus, an endangered species of Morocco and Algeria. Macaques avoided areas used by local shepherds, to reduce the risk of attack by shepherds' dogs, but approached roads to increase the chances of provisioning by tourists. Herding route and road use varied seasonally in line with levels of human use, suggesting that macaques may be navigating their environment strategically (in space and time) to balance food acquisition and risk avoidance.